Crystalline and molecular structure of novel anion-radical salt (N-Et-Pz)(TCNQ)₃ (Pz is pyrazine) - Ziolkovskiy, D.V.; Kravchenko, A.V.; Starodub, V.A.; Kazheva, O.N.; Khotkevich, A.V. (Functional Materials, 2005)
Crystalline and molecular structure of previously synthesized by the authors anion-radical salt (ARS) 7,7,8,8-tetracyanoquinodimethane (TCNQ) of an unusual [N-(H₅C₂)-Pz](TCNQ)₃ composition (where Pz is pyrazine) has been determined. The structure of the given ARS is also unusual because unlike most of structures known it consists of bulks formed by two А and С TCNQ types, particles of the third В type being located at the angle of 117.7 and respectively 117.4 degrees relatively to them. С type particles interact appreciable with pyrazine cations through pyrazine non-alkylated nitrogen atom. В-type particles as well as TCNQ particles in columns, possess an appreciable charge (about -0.3).Such a peculiarity of structure renders ARS electronic system some what two-dimensional that is unusual for TCNQ ARS and agrees with the electrophysical measurements. Определена кристаллическая и молекулярная структура синтезированной ранее авторами анион-радикальной соли (АРС) 7,7,8,8-тетрацианохинодиметана (TCNQ) необычного состава [N-(H₅C₂)-Pz](TCNQ)₃, где Pz - пиразин. Структура данной АРС также необычна - в отличие от большинства известных структур, она состоит из стопок, образованных двумя типами TCNQ - А и С, перпендикулярно которым расположены частицы третьего типа - В. Частицы типа С заметно взаимодействуют с катионами пиразина посредством неалкилированного атома азота пиразина. Частицы типа В, как и частицы TCNQ в стопках, обладают заметным зарядом (около -0,3). Такая особенность структуры придает электронной системе АРС определенную двумерность, необычную для АРС TCNQ, и согласуется с результатами электрофизических измерений. Визначено кристалiчну i молекулярну структуру синтезованої авторами ранiше анiон-радикальної солi (АРС) 7,7,8,8-тетрацiанохiнодиметану (TCNQ) незвичайного складу [N-(H₅C₂)-Pz](TCNQ)₃, де Pz - пiразин. Структура даної АРС також незвичайна - на вiдмiну вiд бiльшостi вiдомих структур, вона складається зi стопок, утворених двома типами TCNQ - А та С, перпендикулярно яким розташованi частки третього типу - В. Частки типу С помiтно взаємодiють з катiонами пiразину за допомогою неалкильованого атому азоту пiразину. Частки типу В, як i частки TCNQ у стопках, мають помiтний заряд (близько -0,3). Така особливiсть структури додає електроннiй системi АРС певну двомiрнiсть, незвичайну для АРС TCNQ, i добре узгоджується з результатами електрофiзичних вимiрiв.